Order-2 extrapolated implicit runge-kutta methods with smoothing for solving ordinary differential equations - Amira Ismail (Tanjong Malim, 2015)
Order-2 extrapolated implicit runge-kutta methods with smoothing for solving ordinary differential equations by Amira Ismail